Total phenolic contents and antioxidant scavenging capacity in free and bound extracts of Christia vespertilionisis (daun rerama) - Mat Jusoh, Hanapi; Zulkarnail, Mohamad Zharif; Haron, Normah (IIUM Press, 2019)
Introduction:Christia vespertilionisis is a plant herb that has been used traditionally due to its benefits for potentially to treat some disease. It contain potential phytochemical compound that can be a component of drugs or natural products. This study was conducted to investigate the total phenolic content and its antioxidant radical scavenging activity on C. vespertilionisis. Hence, a series of test in determining the total phenolic content in three different type of extractions was conducted and its relationship with antioxidant scavenging activity was studied. The C. vespertilionis’s powder was extracted with 80% methanol and hydrolyzed with HCI and NaOH. The total phenolic content was determined using Follin-Ciocalteu and DPPH assay was used for antioxidant activity. Based on the test, the total phenolic content of all extracts was 9.13± 0.13 mg of GAE/g with insoluble bound extracts revealed a highest value of 4.94 ± 0.042 mg of GAE/g followed by soluble bound and free phenolic extracts with (3.16± 0.28 and 0.98 ± 0.07 mg of GAE/g respectively), (p<0.05). The antioxidant scavenging capacity extracts of IC50 showed that insoluble bound extracts showed lowest value (38.13 ± 0.65mg/ml) followed by soluble bound extracts and free phenolic extracts with (39.54 ± 0.77 and 42.59 ± 1.69mg/ml respectively).